Application of Health Belief Model of Tertiary Prevention Behavior in Elderly People with Hypertension: A Multilevel Analysis - Hallisa’tu Zahro; Argyo Demartoto; Bhisma Murti (Journal of Health Promotion and Behavior, 2025)
Background: The health of the elderly is influenced by various risk factors and changes from within themselves and their environment. These various conditions can affect health problems, functional status, level of independence and quality of life of the elderly. Deterioration of health in the elderly can manifest in a variety of diseases, including hypertension. Efforts to control the incidence of hypertension can be done through the provision of health education about hypertension, which aims to raise awareness of hypertensives about the concept of hypertension, complications, and how to overcome. This study aims to examine the application of the Health Belief Model (HBM) as a predictor by taking into account the contextual effects of the Elderly Integrated Healthcare Posts in Kepanjen, Malang, East Java, Indonesia. Subjects and Method: This study was an observational analytical study with a cross-sectional approach using a multilevel analysis model. The population in this study was all elderly people with hypertension at the Elderly Integrated Healthcare Posts in the working area of Kepanjen Community Health Center, Malang, East Java, Indonesia. The sample in this study was 200 elderly with hypertension at the Elderly Integrated Healthcare Posts in the Kepanjen Community Health Center Working Area, Malang, East Java, Indonesia. The study used the Stratified Sampling technique at the healthcare level (Elderly Integrated Healthcare Posts), and Stratified Random Sampling in the selection of the elderly. Results: Tertiary prevention behavior among elderly with hypertension increased with high self-efficacy (b= 0.57; CI 95%= 0.39 to 0.73; p<0.001), cues to action (b= 0.27; CI 95%= 0.35 to 1.71; p<0.001), female gender (b= 0.76; CI 95%= 0.10 to 0.42;  p<0.001), age 70-90 years (b= 0.37; CI 95%= -0.01 to 0.75; p= 0.060). Integrated health posts for elderly on the tertiary prevention behavior of hypertension. The Integrated Healthcare Posts had contextual effect on tertiary prevention behavior (ICC=29.87%; p<0.001). Conclusion: Tertiary prevention behavior of hypertension in the elderly increases with high self-efficacy, cues to action, female gender, age 70-90 years.